2017
DOI: 10.1016/j.eurpsy.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of one-to-one peer support for patients with severe mental illness – a randomised controlled trial

Abstract: The findings suggest that one-to-one peer support delivered by trained peer supporters can improve self-efficacy of patients with severe mental disorders over a one-year period. One-to-one peer support may be regarded as an effective intervention. Future research should explore the impact of improved self-efficacy on clinical and social outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 30 publications
4
105
1
9
Order By: Relevance
“…Reviews of peer interventions for persons with serious mental illnesses, usually incorporating a small but significant number of individuals with BD, have demonstrated modest evidence from RCTs and other controlled studies suggesting that there are important improvements in self‐efficacy and reduction in self‐stigma 106, 107, 108, 109. The largest peer intervention study involving BD allocated 153 individuals to attend 21 weekly group psychoeducation events, with another 151 assigned to attend 21 weekly group peer support events.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…Reviews of peer interventions for persons with serious mental illnesses, usually incorporating a small but significant number of individuals with BD, have demonstrated modest evidence from RCTs and other controlled studies suggesting that there are important improvements in self‐efficacy and reduction in self‐stigma 106, 107, 108, 109. The largest peer intervention study involving BD allocated 153 individuals to attend 21 weekly group psychoeducation events, with another 151 assigned to attend 21 weekly group peer support events.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…), with improved self‐efficacy indicated in newer trials (Mahlke et al . ). Qualitatively, hope and strength of social networks have been explored as important outcomes for people in receipt of support from PW (Walker and Bryant ).…”
Section: Introductionmentioning
confidence: 97%
“…The employment of PW by mental health service organisations is increasingly common internationally (Gillard et al 2013). Recent reviews have indicated the impact of peer support in mental health services on outcomes such as hope, empowerment and self-rated recovery (King andBender Simmons 2018, Lloyd-Evans et al 2014), with improved self-efficacy indicated in newer trials (Mahlke et al 2017). Qualitatively, hope and strength of social networks have been explored as important outcomes for people in receipt of support from PW (Walker and Bryant 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The peer support workers were also viewed as role models for recovery and regarded as easy to build rapport with [5,6]. Other positive outcomes suggested in the literature [4] include increases in quality of life, empowerment, functioning [7][8][9], sense of control and community belonging [10], improved social integration [5,11] and self-efficacy [12], all essential components in recovering from mental illness. Other studies suggest a diminished need for mental health services, reduced substance abuse, fewer hospitalizations, and decreased levels of depression and psychosis [10,13].…”
Section: Introductionmentioning
confidence: 99%